Leishmania RNA virus: when the host pays the toll - Hartley, Mary-Anne; Ronet, Catherine; Zangger, Haroun; Beverley, Stephen M.; Fasel, Nicolas (Frontiers in Cellular and Infection Microbiology, 2012)
The presence of an RNA virus in a South American subgenus of the Leishmania parasite, L. (Viannia), was detected several decades ago but its role in leishmanial virulence and metastasis was only recently described. In Leishmania guyanensis, the nucleic acid of Leishmania RNA virus (LRV1) acts as a potent innate immunogen, eliciting a hyper-inflammatory immune response through Toll-like receptor 3 (TLR3). The resultant inflammatory cascade has been shown to increase disease severity, parasite persistence and perhaps even resistance to anti-leishmanial drugs. Curiously, LRVs were found mostly in clinical isolates prone to infectious metastasis in both their human source and experimental animal model, suggesting an association between the viral hyperpathogen and metastatic complications such as mucocutaneous leishmaniasis (MCL). MCL presents as chronic secondary lesions in the mucosa of the mouth and nose, debilitatingly inflamed and notoriously refractory to treatment. Immunologically, this outcome has many of the same hallmarks associated with the reaction to LRV: production of type 1 interferons, bias toward a chronic Th1 inflammatory state and an impaired ability of host cells to eliminate parasites through oxidative stress. More intriguing, is that the risk of developing MCL is found almost exclusively in infections of the L. (Viannia) subtype, further indication that leishmanial metastasis is caused, at least in part, by a parasitic component. LRV present in this subgenus may contribute to the destructive inflammation of metastatic disease either by acting in concert with other intrinsic ‘metastatic factors’ or by independently preying on host TLR3 hypersensitivity. Because LRV amplifies parasite virulence, its presence may provide a unique target for diagnostic and clinical intervention of metastatic leishmaniasis. Taking examples from other members of the Totiviridae virus family, this paper reviews the benefits and costs of endosymbiosis, specifically for the